Pengaruh Permainan Bowling Binatang terhadap Kemampuan Berhitung di Taman Kanak-Kanak Aisyiyah 1 Kota Bukttinggi - Jefriadi, Jefriadi; Suryana, Dadan (Darul Yasin Al Sys, 2024)
This study is motivated by the media and game tools used by teachers in activities to develop children's counting skills are less effective and varied such as using blackboards and magazines so that the purpose of this study is to determine the effect of animal bowling games on children's counting skills at Aisyiyah 1 Kindergarten, Bukittinggi City. This study uses a quantitative approach in the form of quasi-experimental with the type of nonequivalent control group design which aims to determine the effect of animal bowling games on children's counting skills at Aisyiyah 1 Kindergarten, Bukittinggi City. The population of this study were children in Aisyiyah 1 Kindergarten, Bukittinggi City, totaling 174 children divided into 12 study groups. Sampling with purposive sampling technique, Group B5 and B6 each 12 children. Data collection with an action test using 5 statement items. Data analysis techniques using normality test, homogeneity test and hypothesis testing with the help of SPSS version 26 for windows. The results showed that the data were normally distributed and homogeneous. Furthermore, based on the t test, it is known (2-tailed) is 0.02 <0.05 so it can be concluded that there is an effect of animal bowling games on children's counting skills at Aisyiyah 1 Kindergarten, Bukittinggi City.